Effect of Dietary Inclusion of Commercial Probiotics and Vitamin C on Growth Performance, Nutrient Utilization and Haematological Profile of Clarias gariepinus Fingerlings (Sahel Journal of Life Sciences FUDMA, 2026)
This study evaluated the effects of dietary inclusion of commercial probiotics (Aqua Pro) and Vitamin C on growth performance, nutrient utilisation, and haematological profile of Clarias gariepinus fingerlings. A total of 120 fingerlings were randomly distributed into four treatment groups (T0 – T3) with varying inclusion levels (0,1,2, and 3g/kg) of probiotics and Vitamin C over an 18-week feeding trial. Fish were fed a 45% crude protein diet, and growth indices, feed utilisation parameters and haematological variables were assessed. Results showed significant improvement (p  0.005) in final weight, weight gain, specific growth rate, and protein efficiency ratio with increasing supplementation levels, with the best performance recorded in T3. Feed conversion ratio decreased significantly, indicating enhanced feed efficiency. Survival rate improved from 80% in the control to 93.3% in the highest inclusion group. Haematological parameters (RBC, WBC, PVC, and haemoglobin) were significantly enhanced in supplemental groups, reflecting improved physiological and immune status. Water quality parameters remained within acceptable limits and were not significantly affected by dietary treatments. The study concludes that combined dietary supplementation of probiotics and Vitamin C, particularly at 2 – 3g/kg, enhanced growth performance, nutrient utilisation, and health status of Clarias gariepinus fingerlings.